FAKTOR RISIKO PERILAKU SEKS PADA REMAJA - Kartadarma, Supriyatni; Noorma, Nilam; Indriani, Ririn; Sendra, Eny (Ensiklopedia of Journal, 2025)
Abstract: Risk behavior among adolescents is influenced by various factors, both from the family environment, social, and access to information and health services. Based on an initial survey conducted by the author to several schools in Samarinda City, information was obtained from 35 students, 75% said that they refused if a friend or the opposite sex invited them to watch porn or go on a date, and 65% said that their parents always controlled their activities. The purpose of the study was to determine the risk factors for sexual behavior in adolescents. The research design used in this study was cross sectional. The research was conducted in 5 high schools in Samarinda City. The research was conducted in June 2024. The population in this study were all grade XI students. The sample amounted to 56 people. The sampling technique used in this study was Stratified Random Sampling Technique. Data analysis was done univariate and bivariate. The results showed there was a relationship between the role of parents (p value: 0.000) and the role of peers (p value: 0.014) on sexual behavior in adolescents. It is recommended that health workers maximize adolescent health services in promotive and preventive aspects of reproductive health and sexuality through the PKPR program. Activate adolescent mentoring activities through the PKPR program, and counseling activities. Furthermore, conduct monitoring and evaluation of PKPR program activities in schools so that the program can run continuously with the hope that students are exposed to correct information about adolescent reproductive health and risky premarital sexual behavior can be avoided.Keywords: Parents, Teens, Sex